Clinical features and rare complications in 132 patients with hepatic glycogenosis - Deniz Kor; Fatma Derya Bulut; Burcu Köşeci; Esra Kara; Ezgi Burgaç; İrem Kaplan; Nazmiye Tüzel Gündüz; Halise Neslihan Önenli Mungan (Orphanet Journal of Rare Diseases)
Abstract Background Glycogen storage diseases (GSDs) with liver involvement are classified into subtypes—types 0, Ia, and Ib; III, IV, VI, IX, and XIa, XIb, and XIc, depending on the deficient enzyme. Hypoglycemia and hepatomegaly (except type 0) are hallmarks of the disease; however, muscular and renal tubular involvement, dyslipidemia, and osteopenia can occur. The present study was conducted to highlight the clinical differences and characteristics between types, complications, and long-term outcomes in patients with hepatic GSD. Materials and Methods The records of 132 patients with hepatic GSD, confirmed through genetic analysis, were retrospectively reviewed. Results Of the 132 patients, 55.3% were male. The consanguinity rate was 75, and 53% of the patients had a family history. The age at diagnosis was 34.36 ± 35.1 months. The frequency distribution was as follows: GSD type III (42.4%), Ia (17.4%), IXa (9.1%), Ib (9.1%), IXc (7.6%), VI (6.8%), IXb (4.5%), IV (2.3%), and 0 (0.8%). The most common presenting symptoms were abdominal distention (40.9%), elevated liver transaminases (14.4%), hepatomegaly (13.6%), hypoglycemia (12.1%), family screening (12.1%), growth retardation (4%), and others (3.8%). Hepatomegaly was found in 84.9%, splenomegaly in 20.5%, short stature in 46.2%, underweight in 14.4%, and obesity in 13.5% of the patients. Non-hepatic malignancy was detected in three patients with GSD type III. The twin rate was 6.1%. The rate of short stature was 46.2% at the time of diagnosis, while it was 15.4% in patients who reached adulthood. The number of twin patients was higher than reported in the literature, and structural anomalies such as intestinal duplication cyst, renal artery stenosis, and pulmonary stenosis, which were not previously reported in association with GSD, along with non-hepatic malignancy, were notable findings in our study. Conclusions Liver glycogenosis can present distinct and similar clinical, laboratory, and radiological features, challenging differential diagnosis between types. Our study may guide diagnosing and monitoring common GSDs with hepatic involvement.